2017
DOI: 10.4018/ijksr.2017010104
|View full text |Cite
|
Sign up to set email alerts
|

A Cloud-Based Architecture for Interactive E-Training

Abstract: Cloud-based technologies play a significant role in the technology-enhanced learning domain. The adoption of cloud technologies in the educational environment has a positive impact on the learning process by offering new tools and services to improve and support the learning life cycle, including interactivity. In specific fields, such as clinical skills training, that involve computer-intensive training scenarios, there is an increased demand to deliver training services to a larger number of learners, theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…However, this does not change the fact that students want to use technology [35,38]. That is, they are motivated to participate actively in the learning process [39], but they need support in the meaningful use of technology [25,[40][41][42] to support them in the development of ICT-competence [43]. What follows is that it is professors who can serve as those who scaffold the learning if they have the ICT-competence.…”
Section: Technology-enhanced Learning In Higher Educationmentioning
confidence: 99%
“…However, this does not change the fact that students want to use technology [35,38]. That is, they are motivated to participate actively in the learning process [39], but they need support in the meaningful use of technology [25,[40][41][42] to support them in the development of ICT-competence [43]. What follows is that it is professors who can serve as those who scaffold the learning if they have the ICT-competence.…”
Section: Technology-enhanced Learning In Higher Educationmentioning
confidence: 99%
“…An interactive cloud-based e-learning and training system is proposed [10] to connect the trainers and learners in an effective way together. Quality of Service (QoS), resource utilization and content delivery are the main objectives focused in this work to improve the performance of e-training system.…”
Section: Background Studymentioning
confidence: 99%
“…Sometimes it is assumed that social networks are all online sites which can be accessed through the internet, sometimes it is suggested that there should be clear definitions how social networks are different form Learning Platforms, Learning Management Systems, Virtual Learning environment etc. Authors of this paper will not focus on defining these differences, but rather on benefits of social learning which is supported by using different kind of social media and ICT to scaffold Knowledge Building [29][30][31][32][33][34][35][36][37].…”
Section: Literature Review On the Exploitation Of Social Networking Tmentioning
confidence: 99%
“…Aspects of this reality are manifested in Learning Analytics Research, a branch that sets opportunities to reveal hidden pattern in large volume of data related to learners, academic institution, etc. Also, movement toward [35][36][37][38][39] more open learning using MOOCs (Massive Open Online Courses) is another area which offers full potential for researching student-centered learning analytics such as motivation effects and what to report on students learning. Another focus is learning software provision, which poses new significant challenges for policy makers, learning administrators, and faculty.…”
Section: Literature Review On the Exploitation Of Social Networking Tmentioning
confidence: 99%